2006
DOI: 10.1007/s11255-005-4984-5
|View full text |Cite
|
Sign up to set email alerts
|

Case series: Adult testicular dermoid tumours – mature teratoma or pre-pubertal teratoma?

Abstract: Adult testicular dermoid tumours are rare tumours with no reported potential for recurrent or metastatic spread. Despite this they are currently classified as mature teratoma and managed as if they have equivalent malignant potential. This report describes two cases of adult mature teratoma of dermoid type and questions the classification and pathogenesis of this disease. In one of the cases there was a clear history of a testicular lump arising pre-pubertally, raising the possibility that some adult dermoid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…70 It has been suggested that some may represent persistence of prepubertal teratomas into the postpubertal period. 71 Secondary malignant tumors are recognized if uncommon complication of postpubertal germ cell tumors, as evidenced by studies reporting rhabdomyosarcoma, myxoid liposarcoma, primitive neuroectodermal tumor, chondrosarcoma, melanotic neuroectodermal tumor, and carcinoid tumor in patients who were 12-19 years old. [72][73][74][75][76] However, we are aware of only one case where this occurred in a prepubertal testicular teratoma.…”
Section: Teratomamentioning
confidence: 99%
“…70 It has been suggested that some may represent persistence of prepubertal teratomas into the postpubertal period. 71 Secondary malignant tumors are recognized if uncommon complication of postpubertal germ cell tumors, as evidenced by studies reporting rhabdomyosarcoma, myxoid liposarcoma, primitive neuroectodermal tumor, chondrosarcoma, melanotic neuroectodermal tumor, and carcinoid tumor in patients who were 12-19 years old. [72][73][74][75][76] However, we are aware of only one case where this occurred in a prepubertal testicular teratoma.…”
Section: Teratomamentioning
confidence: 99%
“…Os derivados da endoderme são células do epitélio gastrointestinal, respiratório e glândulas mucosas. Os elementos derivados da mesoderme incluem ossos, cartilagem e músculos (4,5). Há características que podem servir para o diagnóstico diferencial entre cisto dermóide e teratoma testicular, os teratomas testiculares maduros apresentam componentes sólidos e císticos em detrimento de material predominantemente cístico no cisto dermoide e a presença de pelo ou cabelo intralesional é típica do cisto dermoide, aparecendo em mais da metade dos casos (6).…”
Section: Discussionunclassified
“…One study of testicular tumours in prepubertal children found that 74% were benign 86 . Pure teratoma was the most common tumour present in 48% of cases, and, as suggested above, these may be equivalent to adult dermoid cysts 18 . Pure yolk sac tumours comprised 15%, epidermoid cysts 14% and sex‐cord stromal tumours 13% of cases.…”
Section: Introductionmentioning
confidence: 92%
“…However, recently a type of teratoma has been described with no associated ITGCNU, and it has been suggested that these lesions are benign, and are termed dermoid cysts 17 . As paediatric teratomas also lack ITGCNU, it has been suggested that these lesions are in fact paediatric lesions that have persisted to adult life 18 . Therefore, identification of ITGCNU becomes crucial for the correct follow‐up and classification.…”
Section: Introductionmentioning
confidence: 99%